Cell-mediated immunity in patients with paracoccidioidomycosis - Musatti, Chloé Camba; Peraçoli, Maria Terezinha S. [UNESP]; Soares, Angela M.V.C. [UNESP]; Rezkallah-Iwasso, Maria Thereza [UNESP] (Taylor & Francis, 2018)
Paracoccidioidomycosis is similar to other deep mycoses in causing pulmonary disease, which depending on the immunological status of the patient, may either heal spontaneously, disseminate bodywide, or progress to chronic granulomatosis. Resistence is based on cell-mediated immunity since the severity of the disease runs parallel to the impairment of T-cells function. Patients with paracoccidioidomycosis can present a reduced number of lymphocytes due to decrease in the percentage of T lymphocytes, while the number of B lymphocytes is usually normal or elevated. Cell-mediated immunity and humoral immunity are traditional ways of describing the different arms of the immune system. Despite the development of various and more complex in vitro tests for the assessment of cellular immunity, the relatively simple intradermal test remains a useful tool, ocasionally serving in the establishment of the diagnosis. The inhibitory factors present in the plasma of paracoccidioidomycosis patients were also shown to induce morphological and ultrastructural abnormalities, in lymphocytes of patients cultured in autologous plasma.